Symptom trajectories for palliative care inpatients with and without hyperactive delirium in the last week of life. (12th July 2021) - Dai, Yunyun; Walpole, Grace; Ding, Jinfeng; Scanlon, Cian; Ho, Luke; Khoo, Ru Hui; Huang, Chongmei; Cook, Angus; William, Leeroy; Johnson, Claire E.
Abstract: Aims: Hyperactive delirium (HD) is a common and distressing symptom among palliative care patients. This study aimed to describe the characteristics of HD and associated symptoms among palliative care inpatients and evaluate relationships between HD development and symptom trajectories in this population. Design: A retrospective study was conducted. Methods: A retrospective review of medical records was conducted for all patients who died in a large Australian specialist palliative care unit between 1 January and 31 December 2019. Patients were assessed daily using the Symptoms Assessment Scale (SAS) and Palliative Care Problem Severity Scale (PCPSS). Multilevel models were used to estimate the differences in symptoms trajectories in the last 7 days of life between the two groups. Results: Of the 501 included patients, 64.5% (323) had an episode of HD. For 30% (95) of patients, HD occurred prior to admission. Compared with patients without HD, those with HD had significantly higher odds ratios (ORs) for four of the seven SAS symptoms (sleep problems, appetite, fatigue and pain; OR range: 1.94–4.48, p  < .05), and all four PCPSS items (OR range: 2.00–3.00, p  < .05) in the last week of life. Conclusions: Palliative care inpatients commonly experience HD in their last week of life. There are higher levels of symptom distress, complexity, psychological concerns and family/carer concerns among patients with HD compared with those without HD. Impact: The high prevalence of HD, and its association with higher levels of symptom distress, highlights the importance of routine screening and optimal management for HD among palliative care patients. Given the widely recognized challenges facing palliative care professionals in assessment and management of delirium, provision of relevant training among these professionals is recommended.